Why did informal sector workers stop paying for health insurance in Indonesia? Exploring enrollees' ability and willingness to pay. - Muttaqien Muttaqien (Public Library of Science (PLoS), 2021)
Indonesia faces a growing informal sector in the wake of implementing a national social health insurance system-Jaminan Kesehatan Nasional (JKN)-that supersedes the vertical programmes historically tied to informal employment. Sustainably financing coverage for informal workers requires incentivising enrolment for those never insured and recovering enrolment among those who once paid but no longer do so. This study aims to assess the ability- and willingness-to-pay of informal sector workers who have stopped paying the JKN premium for at least six months, across districts of different fiscal capacity, and explore which factors shaped their willingness and ability to pay using qualitative interviews. Surveys were conducted for 1,709 respondents in 2016, and found that informal workers' average ability and willingness to pay fell below the national health insurance scheme's premium amount, even as many currently spend more than this on healthcare costs. There were large groups for whom the costs of the premium were prohibitive (38%) or, alternatively, they were both technically willing and able to pay (25%). As all individuals in the sample had once paid for insurance, their main reasons for lapsing were based on the uncertain income of informal workers and their changing needs. The study recommends a combination of strategies of targeting of subsidies, progressive premium setting, facilitating payment collection, incentivising insurance package upgrades and socialising the benefits of health insurance in informal worker communities.